31.5k views
1 vote
Solve for this problem using elimination.

Solve for this problem using elimination.-example-1
User Jay Kreps
by
5.3k points

1 Answer

4 votes

Answer:

There is no solution to this system.

Explanation:

To solve this problem solve the second equation for y.

2x + y = 9

y = -2x + 9

Now that we have the value of y, we can put that in for y in the first equation and solve for x.

3y = -6x + 4

3(-2x + 9) = -6x + 4

-6x + 27 = -6x + 4

27 = 4

Because this is a false statement, we know that this system has no solution.

User Franz Ebner
by
6.0k points